The effect of Adey and Shayer Model on the Acquisition of the Grammatical Concepts by Preparatory School Students and Developing Their Attitudes towards Arabic Grammar Subject - Mohammed Salman, Huda; Saleh Hussien, Falah (Opción, 2019)
The current study aims at finding out the effect of Adey and Shayer Model on the acquisition of the grammatical concepts by preparatory school students and de- veloping their attitudes towards Arabic grammar subject .The sample of the study comprises (70) preparatory school students .Two instruments were adopted in that the first one is a test of the grammatical concepts with (30) items ,while the second instrument an attitude test towards Arabic grammar subject with ( 29) items .The psychometric features of the two instruments were verified .Results show that there is a statistically significant difference between the two means of the grammatical concepts acquisition of the both the experimental group and the control one and in favour of the experimental group , and there is a statically significant difference between the mean of the two means of the developing the students’ attitudes of both the experimental group and the control one towards Arabic Grammar Subject and in favour of the experimental group